Stonewall Jackson's Campaign in the Shenandoah Valley of Virginia - Allan, William (London Hugh Rees, Ltd., 1912)
The operations of General T.J. Jackson in the Valley of Virginia, during the first half of the year 1862, constitute one of the most brilliant and interesting episodes of the great Civil War. The theatre on which they took place afforded a quick and easy approach to the Federal capital and to the Northern states. The mountains and rivers of the Valley gave to an active and skilful commander many opportunities of neutralizing great disparity of force. The celerity, energy, and skill which Jackson manifested on this field excited the admiration of his countrymen and produced a feeling nearly akin to consternations among his foes. His campaign had a most important bearing upon all the military operations in Virginia in the spring and summer of 1862, for he caused to be detained, for the defence of Washington and Maryland, forces in the aggregate four or five times as numerous his own, and thus in fatal degree hampered and paralyzed McClellan. The story of this campaign will always be interesting to the actors in it on both sides, and not merely to them; to the student of military art it affords an admirable example of an aggressive-defensive campaign, and one of the best instances in modern times of the degree to which skill and daring may neutralize superiority of numbers and resources. Our aim has been to give an accurate history of this campaign from official sources.
Include Maps, Notes and Index.
Stonewall Jackson's Campaign in the Shenandoah Valley of Virginia, from November 4, 1861, to June 17, 1862.
Keywords: Romney Campaign (1861-1862) -- Shenandoah Valley Campaign (1862) -- American Civil War (1861-1865)